Relationship of Smoking Status and Severity of Inpatient Community Acquired Pneumonia (CAP) - Karisma, Risa Septia; Sahrun, Sahrun; Ronanarasafa, Ronanarasafa; Priono, Risky Irawan Putra (MAGNA MEDICA Berkala Ilmiah Kedokteran dan Kesehatan, 2023)
Background: Pneumonia is an inflammation of the lung parenchyma. Pneumonia became the first most lung health problem in West Lombok. Smoking is one of the main factors in CAP. This study aims to determine the relationship between smoking status and severity of inpatient CAP patients.Methods: Case control study design was used with medical record measurement tools. A total of 70 samples were taken using a purposive sampling technique for community pneumonia patients (CAP) at Patut Patuh Patju Regional General Hospital Gerung, West Lombok in November 2021-October 2022. Calculation of the severity of CAP patients used the PSI score. Results: The results obtained a p-value of 0.000 (p-value <0.05) for smoker status with a degree of severity of CAP, and a p-value of 0.064 (p-value> 0.05) for a degree of smoking with a degree of severity of CAP. The estimated risk (OR) for smoking status with the severity of CAP is 19.33.Conclusions: There is a significant relationship between smoking status, but not with smoking degree, to severity of CAP at Patut Patuh Patju Gerung Regional General Hospital, West Lombok.